Vegetative Propagation of Wood Apple (Feronia limonia Correa) - Hiwale, S.S.; Dhandar, D.G.; Bagle, B.G. (Indian Journal of Agroforestry, 2020)
Wood apple is one of the under utilized fruits, indigenous to our country. It is one of the most hardy fruit tree and can be cultivated under harsh soil and climatic conditions in rainfed areas. There are no regular plantations but stray seedling trees are found growing all over India. Lot of variability exists in the species and there is a possibility to identify the elite types which can be multiplied vegetatively true to type on large scale. Therefore studies were carried out to identify best method and time suitable for large-scale multiplication of wood apple. The results clearly indicated that soft wood grafting was the best method when one-year-old desi rootstock was used for propagation. Maximum success was obtained when grafting was done in the month of February. Comparative performance of in-situ soft wood grafting and grafting in nursery and then transplanting in the field indicated that on the basis of growth parameters in-situ soft wood grafting was more vigorous as compared to nursery grafting.